Electrochemical detection of uric acid on exfoliated nanosheets of graphitic-like carbon nitride (g-C3N4) based sensor - Chan-Park, Mary Bee Eng (2019)
A highly sensitive, selective and stable electrochemical sensor for detection of uric acid (UA) in aqueous solution has been successfully developed by deposition of exfoliated graphitic-like carbon nitride (g-C3N4) nanosheets on glassy carbon electrode (GCE). The synthesized g-C3N4 was confirmed by X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) and Raman spectroscopies. Field-emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM) were used to investigate the crystalline structure of g-C3N4. The elemental composition was characterized by energy-dispersive X-ray spectroscopy (EDXS). Compared to bare GCE, exfoliated g-C3N4 nanosheets (NS) modified GCE exhibited higher catalytic current for UA electro-oxidation at reduced over potential in 0.1 M phosphate buffered saline solution (PBS), which is essential to discriminate interfering analytes. g-C3N4 NS modified GCE showed a linear relationship between the electrochemical signal and the UA concentration from 100 to 1000 μM with fast response by differential pulse voltammetry (DPV). The common interferent molecules such as dopamine, ascorbic acid, folic acid, paracetamol, lactic acid, oxalic acid, cysteine, and ciprofloxacin were tested in 0.1 M PBS for the g-C3N4 NS modified GCE. It was found that these molecules did not affect the oxidation current of UA when they co-existed in the same buffer solution. Moreover, the modified sensor probe was tested for UA in urine samples with satisfactory recovery values. The proposed sensor offers high accuracy, sensitivity, simple fabrication and low cost. We suggest that g-C3N4 NS based sensor can be useful for UA analysis in medical, environmental, food and industrial applications.